The Influence of Predictor Factors on Entrepreneurship Career Inclination: Benefit of Entrepreneurship Career as a Mediator/ Pengaruh Faktor Peramal Terhadap Kecenderungan Kerjaya Keusahawanan: Kebaikan Pekerjaan Keusahawanan Sebagai Pengantara (Sains Humanika, 2020)
This research aimed to study the influence of predictor factors on inclination toward entrepreneurship career involving the benefits of entrepreneurship career as a mediator. The method of the study is quantitative approach using 161 sets of questionnaires distributed by simple random method among the form four students from entrepreneurship club in 16 secondary schools in Terengganu. Data was analysed using Statistical Package for the Social Sciences (SPSS) involving descriptive test, Multiple Regression and Hierarchical Regression. Descriptive test finding found that most of the respondents have entrepreneurship career inclination at the high level. The findings of the Multiple Regression analysis found that predictor factors such as social norm, entrepreneurship skills and role model influenced entrepreneurship career inclination. Meanwhile, Hierarchical Regression analysis found that social norms, entrepreneurship skills and role model could influence the entrepreneurship career inclination through mediator the benefits of entrepreneurship career. The findings from these two analysis found that role model is the most dominant factor in influencing of entrepreneurship career inclination directly or indirectly by using the benefits of entrepreneurship career as a mediator. The findings of this study add value to the existing findings of the predictor factors affecting the inclination and the benefits of entrepreneurship career as mediator.Â
Keywords: Predictor factor; entrepreneurship career inclination; benefif of entrepreneurship career; secondary school student; entrepreneurship club